Diagnóstico y Evaluación de la contaminación del aire, producida por el trasporte público - urbano: Caso compañía Vencedores de Pichincha Vepiex S.A. - Cervantes Puente, Alex Renato (2005)
The present investigation describes the diagnosis and evolution of the air pollution, produced by public transport - urban: case Compañía Vencedores e Pichincha, in the city of Quito, taking as reference the institutional framework, the number of users, the number of units, operators of the system, describing some results obtained, and the obstacles encountered in the service process offered by this Company private public urban transport, taking into account the population that benefits, adding to it the lack of adequate road signs, the monopoly of municipal transport, safety and environmental hygiene; which has located the problems of the mass private transport service as an obstacle to the municipal authorities. It is undeniable that today, in the capital city, air pollution and noise, exceed the established control standards, making the development of urban and rural transport projects that optimize the use of the regulatory standards for prevention, safety and conservation of the scarce natural, human and material resources available to the capital of the Ecuadorians. Therefore, it is essential to first create and implement awareness in the class of the flyer, an environmental education, with security and industrial hygiene that benefits the environment and what is more to the current generations as future of our society, because all We are users of these transport units. The air of the city of Quito is no longer the same, since the beginning of the era oil industry, as a result of which transport was significantly increased, adds the disorderly urban and population increase towards the big city, which attracted certain factors that cause pollution of the environment, congestion, the growth of factories, urban transport companies - rural areas, inadequate population settlements, the same ones that are disorganized and poorly planned. To the exposed thing the monopoly of the current municipal transportation, which is leading day to day to a constant crisis in private transportation.